Around amicus curiae - Bazán, Víctor (2009)
The Inter-American Court of Human Rights is aware that judges and domestic courts are subject to rule of law and forced to apply provisions in force in their body of laws. But, when a State has ratified an international treaty such as the American Convention, the judges are forced to observe them. Article 2.3 of the applicable Regulations of the Inter-American Court of Human Rights, partially reformed and renewed, defines the term amicus curiae as «the person strange to the dispute and proceeding who offers the Court ideas about the events contained in a lawsuit or formulates juridical considerations on the matter of the proceeding through a document or pleading in a hearing». Therefore, they have a significant value for the strengthening of the inter-American system for the protection of human rights, through reflections provided by members of the society, which contribute to the debate and extend the facts available to the Court. In summary, an amicus curiae is a plausible instrument which should be explored in order to invigorate the judicial discussion and extend deliberation margins, through publicly analyzed arguments, contributing to human rights defense and performance and contributing to the rendering of reasonable judgments resulting from a sustainable degree of agreement among the community